Avaliação toxicológica da exposição crônica do extrato de goji berry (Lycium barbarum) em Caenorhabditis elegans - Rodrigues, Cristiane De Freitas (2023)
Nowadays, people make use of food supplements to support their health. On the other hand, it is not known for sure what the effects of long-term use of supplements are, and the possibility of accumulation in another region, beyond what is expected. Therefore, studies are needed to evaluate the long-term actions of supplements, detailing their dose response in relation to pro-oxidant/toxicological activities. Among the various supplements consumed, Goji berry (Gb) has stood out for its bioactive compounds, such as polyphenols and polysaccharides, but mainly for antioxidant actions and possible lipid modulations. However, the dose-response of Gb use is unknown in relation to its low dose for antioxidant effect and high dose for pro-oxidant/toxicological effect.Besides not being elucidated how the supplement behaves in the long term. In this context, the study aims to evaluate the dose-response relationship against prolonged exposure to Goji berry extract (GBE) in Caenorhabditis elegans. The Gb fruit in the form of a berry was purchased in the local market, and a hydroalcoholic extraction was carried out for the necessary analyses. To standardizing concentrations, calculations were based on the content of total phenolic compounds (Folin-Ciocalteumethod -µg gallic acid equivalent/µL -µg GAE/µL). For the biological tests, approximately 3000 worms (L1) were used, which were exposed to different concentrations of 0.025, 01,0.5, 1.5, 2 µg GAE/µL GBE, for 48 hours. First, a dose-response curve was obtained to select the concentrations to be used. As the experiments were carried out, it was observed that concentrations greater than 1.5 and 2 µg GAE/µL present a high degree of toxicity, as well as an increase in the generation of reactive species and an increase in lipid peroxidation, promoting an imbalance in the antioxidant activity defenses, thus harming the life of the worm. Thus, oxidative damage also influenced behavioral parameters, omega turn, reversal and swimming. Thus, suggesting that prolonged exposure toGBE on the reverse side, at the concentrations tested, could be affecting motor signaling pathways, triggering dysfunctional changes due to the increase in reactive species.